Stability of quantitative trait loci for growth and wood properties across multiple pedigrees and environments in Eucalyptus globulus. Issue 4 (20th March 2013) - Freeman, Jules S.; Potts, Brad M.; Downes, Geoffrey M.; Pilbeam, David; Thavamanikumar, Saravanan; Vaillancourt, René E.
Summary Eucalypts are one of the most planted tree genera worldwide, and there is increasing interest in marker‐assisted selection for tree improvement. Implementation of marker‐assisted selection requires a knowledge of the stability of quantitative trait loci (QTLs). This study aims to investigate the stability of QTLs for wood properties and growth across contrasting sites and multiple pedigrees of Eucalyptus globulus. Saturated linkage maps were constructed using 663 genotypes from four separate families, grown at three widely separated sites, and were employed to construct a consensus map. This map was used for QTL analysis of growth, wood density and wood chemical traits, including pulp yield. Ninety‐eight QTLs were identified across families and sites: 87 for wood properties and 11 for growth. These QTLs mapped to 38 discrete regions, some of which co‐located with candidate genes. Although 16% of QTLs were verified across different families, 24% of wood property QTLs and 38% of growth QTLs exhibited significant genotype‐by‐environment interaction. This study provides the most detailed assessment of the effect of environment and pedigree on QTL detection in the genus. Despite markedly different environments and pedigrees, many QTLs were stable, providing promising targets for the application of marker‐assisted selection.